Teaching foreign languages to seniors: Some insights from pre-service EFL teachers - Gabryś-Barker, Danuta (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2020)
The study of adult-learning does not have a very long tradition, as it was initiated by Malcolm Knowles in the United States in the middle of the 20th century. However, a fast- growing interest in this area of research can now be observed due to ageing populations, especially in the European context (Ramirez Gomes 2016, Gabryś-Barker 2018). Among others, it is perceived as an acute problem in Polish society Thus, numerous institutions have come into being attempting to accommodate seniors in modern society by offering a wide range of educational opportunities, among them the Third Age Universities (Gabryś-Barker 2018, Grotek 2018). The main focus of this article lies in assessing the adequacy of teacher training for the specific context of teaching foreign language to late adults by pre-service EFL teachers. The data demonstrates clearly an urgent need for more instruction in teaching a FL to senior learners. It appears that the pre-service teachers participating in the survey have a very critical view of their present training programme. Thus, their awareness of the specificity of the process is not very well-developed and ideas proposed are not well-grounded in theory, instead they follow intuitive and experiential assumptions. This text is a tribute to Professor Graca Pinto`s achievements in the educational research on (late) adults, who along with such scholars in America as first Eduard C. Lindeman or later on Malcolm Knowles was one of the first scholars in Europe to undertake and pursue this important research area in her admirable scholarly career. Muito obrigada.